“Foram os livros que escrevi que me fizeram” : o espaço autobiográfico de José Saramago - Laitano , Paloma Esteves (2015)
This study aims to define the José Saramago’s autobiographical space by identifying the expression of subjectivity present in his chronicles, his memoir (confessional literature) and his novels (fictional literature) of the portuguese writer. The analysis of the texts that make up the corpus has privileged, from each one of the texts, which can be related with three themes: man/ideology, man/past and man/literature. Based on the theoretical formulations, especially the one’s by Paul Ricoeur and Javier del Prado Biezma, this study demonstrates the identification of recurrent thematic fields in the narrative and structural marks left by the Self in the texts. These aspects made it possible to trace the presence of the subject that is expressed through writing and also the definition of a Saramago’s autobiographical space.